Acupuncture Treatment at Suo-Xi Specialized Hospital in Prolapsed Lumbar Intervertebral Disease (PLID): A Case Study - SM. Shahidul Islam; Hui Hui Li; Sabina Yasmin; Mohammad Shajib Sheik (Asian Journal of Medical Research, 2023)
Background: Low back pain and sciatica are two of the most common types of medical complaints. This change will result in fewer hours worked, which will relieve pressure on the economy on a national level. These folks must first complete a comprehensive medical examination before initiating therapy for their condition. Inadequate medical or surgical therapy increases the risk of this developing, making it more probable that it will occur. The purpose of this research is to investigate whether or whether traditional PLID therapy may be improved by acupuncture. Methods: This inquiry took place at Suo-Xi Hospital (Acupuncture) at Shaan Tower, Chamelibag, Shantinaga, Dhaka, Bangladesh. A 54-year-old male patient has been complaining of lower back discomfort for the last fifteen years. Results:  The results of the follow-up study were excellent. The patient's lower back pain, which he had been suffering for fifteen years, was no longer present. Conclusion: Patients with PLID may benefit from acupuncture, according to this research.